Length of Stay: A Case of Northern Norway - Prebensen, N.; Altin, M.; Uysal, Muzaffer (Routledge, 2015)
Abstract: Length of stay (LOS) is one of the most commonly used variables in visitor surveys. The economic theory of consumer behavior postulates that a rational consumer maximizes utility subject to his /her budgetary restrictions. The objective of this study was to combine socio-demographic and travel behavior variables in order to examine the determinants of LOS for northern Norway as a vacation destination. Using data generated from a cross-sectional survey of visitors, the study employed truncated negative binomial regression analysis to examine the relationship between LOS and selected determinants of LOS. The results indicated that not all demographic variables but gender of visitors and income influenced LOS. Motivation, perception of the destination (brand personality) and perceived experience value also exerted varying degrees of influence on LOS. Visitors perceiving northern Norway as wholesome, cheerful, charming and sporty/outdoorsy stayed longer in the destination. Further, those with strong social motivations and experiences also stayed longer. Subsequently, it is recommended that managers carry out goal-directed product development and promotion strategies for attractions in northern Norway.